2012
DOI: 10.1126/science.1227356
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Simulation in Neuroscience

Abstract: Abstract:Modeling work in neuroscience can be classified using two different criteria. The first one is the complexity of the model ranging from simplified conceptual models that are amenable to mathematical analysis to detailed models that require simulations in order to understand their properties. The second criterion is that of direction of workflow, which can be from microscopic to macroscopic scales (bottom-up) or from behavioral target functions to properties of components (top-down). We review the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 105 publications
(116 reference statements)
1
111
0
4
Order By: Relevance
“…In addition, our results highlight the connection between the temporally distributed predictive learning (6,7,11,17) and abstract structured representations (8,14). The remarkable fit of the parameters derived from this neural model with a Bayesian model derived from very different considerations reinforces the idea that the temporal integration mechanisms in our neural model provide a good account of human information integration over time.…”
Section: Resultssupporting
confidence: 57%
“…In addition, our results highlight the connection between the temporally distributed predictive learning (6,7,11,17) and abstract structured representations (8,14). The remarkable fit of the parameters derived from this neural model with a Bayesian model derived from very different considerations reinforces the idea that the temporal integration mechanisms in our neural model provide a good account of human information integration over time.…”
Section: Resultssupporting
confidence: 57%
“…As large-scale simulations 4 have become important in many scientific fields, such as cosmology and climate research, supercomputer infrastructures have become an indispensable tool. This is certainly also the case in neuroscience (Gerstner et al 2012) and a broad spectrum of largescale models and simulations is found in neuroscience (De Garis et al 2010). Examples include the "Blue Brain" (Markram 2006), the "SyNAPSE project" (Systems of Neuromorphic Adaptive Plastic Scalable Electronics; Ananthanarayanan et al 2009), a large-scale model of the mammalian thalamocortical systems (Izhikevich & Edelman 2008), and the SPAUN model (Semantic Pointer Architecture Unified Network; Eliasmith et al 2012).…”
Section: Technology -Ethical Issues Of the Simulation Approachmentioning
confidence: 99%
“…If the processing algorithm produces outputs that are comparable to human (or animal) responses, then there are evidences that the theoretical model is accurate and has explanatory power. Therefore, computational simulation is a useful strategy to test theories about mental functioning and cognition, allowing to establish their strengths and weaknesses (e.g., Gerstner, Sprekeler, & Deco, 2012).…”
Section: Basic Psychological Processes and Programming Languagesmentioning
confidence: 99%